2013
DOI: 10.3201/eid1910.130883
|View full text |Cite
|
Sign up to set email alerts
|

Human Infections with New Subspecies ofCampylobacter fetus

Abstract: Campylobacter fetus subsp. testudinum subsp. nov. is a newly proposed subspecies of C. fetus with markers of reptile origin. We summarize epidemiologic information for 9 humans infected with this bacterium. All cases were in men, most of whom were of Asian origin. Infection might have been related to exposure to Asian foods or reptiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 9 publications
(8 reference statements)
2
53
0
3
Order By: Relevance
“…Although for reptilian C . fetus there appears to be an association between contact with reptiles and infection in humans [6], [12], [13], to this date, no such association has been described for the other Epsilonproteobacteria species. The growing number of reptiles kept as pets in some European countries [27] and increased farming of reptiles, predominantly freshwater turtles for human consumption, in Asian countries [28], might increase the risk of reptilian derived Epsilonproteobacteria infections in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Although for reptilian C . fetus there appears to be an association between contact with reptiles and infection in humans [6], [12], [13], to this date, no such association has been described for the other Epsilonproteobacteria species. The growing number of reptiles kept as pets in some European countries [27] and increased farming of reptiles, predominantly freshwater turtles for human consumption, in Asian countries [28], might increase the risk of reptilian derived Epsilonproteobacteria infections in humans.…”
Section: Discussionmentioning
confidence: 99%
“…in reptiles from captive populations in Europe and found that 63/163 (38%) of lizards were positive using PCR detection and 18/163 (11%) were positive using culture. Additionally, a genetically distinct variant of Campylobacter fetus has been isolated in the USA from both reptiles and humans who had direct or indirect contract with the reptile [28]. This is also supported by a study from Taiwan that detected C. fetus from 6.7% (12/179) of faeces collected from wild and domestic reptiles [29].…”
Section: Introductionmentioning
confidence: 87%
“…nov. (39). Epidemiologic investigation indicated that afflicted individuals were largely Asian men who reported consumption of Asian foods or had previous exposure to reptiles (40).…”
Section: Facultative Gram-negative Rodsmentioning
confidence: 99%